DOITrees Revisited: Scalable, Space-Constrained Visualization of Hierarchical Data - Jeffrey Heer; Stuart K. Card (AVI'04: Proceedings of the Working Conference on Advanced Visual Interfaces, 2004)
This paper extends previous work on focus+context visualizations of tree-structured data, introducing an efficient, space-constrained, multi-focal tree layout algorithm (TreeBlock) and techniques at both the system and interactive levels for dealing with scale. These contributions are realized in a new version of the Degree-Of-Interest Tree browser, supporting real-time interactive visualization and exploration of data sets containing on the order of a million nodes.